Polarization-sensitive infrared photodetectors based on van der Waals heterojunction with the unilateral depletion region. (8th December 2022) - Zhang, Kun; Chen, Yue; Liu, Anna; Deng, Ke; Gu, Yue; He, Ting; Wang, Yang; Li, Qing; Wang, Zhen; Ge, Haonan; Zhong, Fang; Wang, Peng
Abstract: In recent years, polarization infrared detection technology has made great progress and has been successfully applied in various fields such as national defense, astronomy, and civil applications. However, so far, the integration of micro polarizers and infrared photodetectors is still a big challenge since metal microstructures are severely limited in their size. As anisotropic two-dimensional (2D) materials rapidly appear, this distinctive polarization characteristic regardless of the size provides new freedom to polarization infrared photodetectors. In this paper, a van der Walls heterojunction with the unilateral depletion region was constructed to obtain polarization-sensitive infrared photodetection, in which black phosphorus (BP) serves as a natural polarizer. BP/PtS2 infrared photodetectors possess a fast response speed (the rise time is 56 μ s and the fall time is 64 μ s). At the same time, these photovoltaic detectors achieve a high detectivity of 4.47 × 10 10 cm Hz 1/2 W −1 at 830 nm. Using the anisotropic structure of BP, the photovoltaic polarization detector was realized, and its polarization extinction ratio at 830 nm was 2.66 (3.18 @ 1310 nm and 2.63 @ 1550 nm). This work discovers the potential value of anisotropic 2D materials in infrared polarization-sensitive photodetection and provides a possibility for a new infrared polarization detection system.